Research on prominent biosafety issues in the field of public health in China: a review - Qifan YANG; Yuping WANG (Editorial Office of Chinese Journal of Public Health, 2023)
On October 17, 2020, China officially passed the Biosafety Law of the People's Republic of China, which lists biosecurity as an important part of national security and clarifies the important status of biosafety. The development of public health has received wide attention in the context of coronavirus disease 2019 (COVID-19) pandemic. By expounding the scope of biosafety and public health, we review current biosafety risks in the field of public health in China from the aspects of emerging infectious disease outbreaks, laboratory biosafety and microbial resistance for providing a reference to relevant studies and practices.